Adapting Research Protocols During War: The ANCHOR (Analysis of Network Composition, Health Outcomes, and Resilience) Study - Myroslava Filippovych; Ganna Kovalenko; Britt P Skaathun; Joel O Wertheim; Igor Koutsenok; Mariia G Liulchuk; Samuel R Friedman; Pavlo Smyrnov; Tetyana I Vasylyeva (Journal of Epidemiology and Global Health, 2026)
Abstract Background Conducting longitudinal infectious disease research during armed conflicts is important for understanding transmission dynamics and preventing outbreaks. War in Ukraine started in 2014, with the escalation to full-scale invasion in 2022, resulting in massive population displacement, infrastructure destruction, mobility restriction for men, and reduced access to healthcare. The ANCHOR (Analysis of Network Composition, Health Outcomes, and Resilience) study, launched in November 2024, examines how war- and displacement-driven changes affect social networks, HIV risks, and HIV care engagement. Here, we report implementation challenges and adaptations as practical lessons that may inform infectious disease surveillance and research in conflict settings. Methods ANCHOR is a cohort study conducted in Kyiv and Lviv in 2024–2026 that enrolled sexual minority men (SMM) using respondent-driven sampling, with 6- and 12-month follow up of participants testing positive for HIV. Data collection included structured behavioral and social network interviews, HIV rapid testing, viral load (VL) assessment, and HIV genetic sequencing. Results A total of 1,199 SMM were enrolled; of those, 87 tested positive for HIV. Challenges of conducting a research study in an ongoing conflict were identified during the first month of recruitment and prompted protocol revision, incorporating online screening, oral consent, remote interviews, video-assisted HIV self-testing, flexible biospecimen collection. These changes enabled safe completion of study recruitment ahead of the anticipated schedule (within 8 instead of 18 months). Interview follow-up rate was 94% (82/87) at both 6-and 12-month, accompanied by successful biospecimen collection in 61/87 and 45/87 cases at 6-month and 12-month follow-up, respectively. Conclusions Flexible adaptations in response to the war conditions preserved study integrity and safety of study participants and staff. Availability of various modes of biospecimen collection allowed successful completion of clinical and genomic components of the study, including VL testing and HIV molecular epidemiology analyses despite logistical, infrastructural, and security constraints. Longitudinal biospecimen collection remained challenging due to the ongoing migration and displacement. Lessons from the ANCHOR study can support continuity of infectious disease research in conflict settings and among populations facing barriers to participation. Some of these adaptations may also be applicable to routine infectious disease surveillance, although their utility requires further evaluation.